2014
DOI: 10.1007/s11695-014-1212-3
|View full text |Cite
|
Sign up to set email alerts
|

Keeping the Weight Off: Physical Activity, Sitting Time, and Weight Loss Maintenance in Bariatric Surgery Patients 2 to 16 Years Postsurgery

Abstract: Results demonstrate associations between MVPA and high sitting time and weight loss outcomes among bariatric patients in the long term. The implications for long-term weight management and concomitant health outcomes highlight the need for appropriate follow-up and interventions in this unique high-risk patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 54 publications
2
27
1
3
Order By: Relevance
“…Contrary to what has been observed in adults, 18, 24 we did not observe statistically significant associations of physical activity levels or sitting-time with weight-loss maintenance despite there being potentially meaningful mean differences between groups. The majority of participants, similar to adults, 25 were highly inactive and sedentary, regardless of group assignment.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to what has been observed in adults, 18, 24 we did not observe statistically significant associations of physical activity levels or sitting-time with weight-loss maintenance despite there being potentially meaningful mean differences between groups. The majority of participants, similar to adults, 25 were highly inactive and sedentary, regardless of group assignment.…”
Section: Resultscontrasting
confidence: 99%
“…Additionally, several post-operative behavioral factors have been shown to influence weight-loss outcomes. These factors include adherence to food intake guidelines such portion size, 16, 17 physical activity and inactivity, 18 and self-weighing. 17 Whether these post-operative factors influence weight-loss maintenance in the post-bariatric surgery setting among adolescents has yet to be examined.…”
Section: Introductionmentioning
confidence: 99%
“…Intervention staff also encouraged participants in this arm to engage in specific behavioral strategies associated with long-term weight control including breakfast eating, reducing sedentary time, and developing a consistent eating and activity routine. [2628] In addition to this one-time group session, all Standard participants received monthly informational emails from a research assistant that included problem solving strategies to promote physical activity and reduce caloric intake plus access to healthy, low calorie recipes.…”
Section: Methodsmentioning
confidence: 99%
“…Vatier et al () found that decreases in reported television (TV) watching from pre‐op to 1‐year post‐RYGB were inversely associated with changes in fat mass, independently of PA. In another study, self‐reported sitting time was inversely associated, independently of MVPA, with total weight loss and weight loss maintained in patients 2–16 years post‐RYGB (Herman et al, ). Only one study to date has examined the relationship between objectively measured SB and bariatric surgery outcomes, showing a positive association between SB time and current weight in patients 6–18 months post‐op (Chapman et al ., ).…”
Section: The Importance Of Physical Activity and Sedentary Behavioursmentioning
confidence: 99%